2020
DOI: 10.1002/jqs.3183
|View full text |Cite
|
Sign up to set email alerts
|

To what extent did changes in temperature affect China's socioeconomic development from the Western Han Dynasty to the Five Dynasties period?

Abstract: Analysing the contribution of climate and non‐climate change factors to social development and the occurrence of historical events represents important research on the impact of climate change. This study identifies combinations of social subsystem indices affected by temperature changes using the conceptual framework of food security, a priori knowledge and logical reasoning to statistically analyse three 10‐year data series (grain harvest grades, famine indices and economic levels) from the Western Han Dynas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…4B , the period of dynastic succession in China was also a period of frequent meteorological disasters. Previous studies have shown that the historical famines or peasant uprisings were often related to meteorological disasters on an annual time scale, and severe famines and peasant uprisings were often triggered by severe climatic disasters ( Pederson et al, 2014 ; Buckley et al, 2014 ; Tian, Stige & Cazelles, 2011 ; Kelley et al, 2015 ; He, Su & Fang, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…4B , the period of dynastic succession in China was also a period of frequent meteorological disasters. Previous studies have shown that the historical famines or peasant uprisings were often related to meteorological disasters on an annual time scale, and severe famines and peasant uprisings were often triggered by severe climatic disasters ( Pederson et al, 2014 ; Buckley et al, 2014 ; Tian, Stige & Cazelles, 2011 ; Kelley et al, 2015 ; He, Su & Fang, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Beijing Tianjin Hebei was under the jurisdiction of the Governor General of Zhili during the Qing Dynasty, Shanghai was part of Jiangsu Province during the Qing Dynasty, Gansu and Ningxia were also under the same provincial-level administrative region during the Qing Dynasty, and Chongqing was part of Sichuan during the Qing Dynasty. In addition, due to the special natural geographical conditions of the plateau in Tibet, its urban development was restricted in history, and there exist relatively few records regarding its cities in related historical archives 37 . Moreover, the organizational form of the cities in the plateau area was also quite different from that of ordinary cities, so this study regarded it as no urban area.…”
Section: Methodsmentioning
confidence: 99%
“…Similar dynamics were noted in the literature concerning other past collapses, such as Rapa Nui. One exception in regard to this tension is the cause of the collapse of past Chinese societies; a vast majority of articles emphasized the influence of climate change, nevertheless explaining that climate and nonclimate factors were linked, but that the former contributed to the deterioration of the latter (e.g., An et al, 2004;Kidder & Liu, 2017;Feng et al, 2019;He et al, 2020).…”
Section: Past Collapsesmentioning
confidence: 99%